PEMBAJAKAN MUSIK DAN LAGU : SEBUAH KAJIAN YURIDIS BERDASARKAN PERJANJIAN INTERNASIONAL TENTANG PERLINDUNGAN KARYA SENI DAN SASTRA SECARA DIGITAL DI INDONESIA (Universitas PGRI Sumatera Barat, 2012)
AbstractIn recent years, the level of copyright piracy of music and song in several countries,especially Indonesia, Indonesian people are generally more likely to choose pirated CDs thanthe original, with the reasons expensive original works and the price difference very much.Legally, the core problem of music piracy and the song is contrary to Article 2 point (1) BerneConvention for the Protection of Literary and Artistic Works containing that music is a creationand a nationally-protected against the Law No. 19 Year 2002 on Copyright Article 12 paragraph(1). Therefore, the required action from the government in dealing with these problems,. Theauthor would like to discuss the concept of an ideal law enforcement in cases of copyright piracyof digital music and the songs and the dominant factor affecting copyright piracy of music andsong in Indonesia, Factors Affecting Copyright Piracy Music And Songs In Indonesia, amongothers, the factors based economy because they want to seek financial benefits quickly andignoring the interests of creators and copyright holders, cost factors, cultural factors of societyitself so that public awareness of the illegal pirated goods is still very low. The governmentshould issue a form idealdalam concepts governing Perunang-Invitation Copyright in greaterdetail, giving firmness law, legal protection and certainty against copyrigt Indonesia.